Betaine Supplementation to Methionine Deficient Diet Improves Growth Performance, Carcass Characteristics, Blood Parameters and Economic Efficiency of Broilers - T, Susmita (Indian Journal of Animal Nutrition, 2021)
The objective of this study was to evaluate the influence of supplementary betaine on growth performance, carcass traits and some blood parameters in broilers fed methionine deficient diets. a total of two hundred and seventy day-old commercial broiler chicks Cobb 400, were randomly allotted to nine treatments of six equal replicates and each replicate having five birds (9Ã—6Ã—5=270). Nine iso-nitrogenous and is-ocaloric diets consisting of a control diet (CD), 25% and 50% methionine deficient diet and with graded levels of betaine (1.0, 2.0 and 3.0% levels) were formulated and fed to chicks from 1 to 42 days of age. The results revealed that supplementation of betaine at 0.3% level improved (